2020
DOI: 10.1111/jfb.14310
|View full text |Cite
|
Sign up to set email alerts
|

ZebrafishDanio rerioshows behavioural cross‐context consistency at larval and juvenile stages but no consistency between stages

Abstract: Coping style is defined as a set of individual physiological and behavioural characteristics that are consistent across time and context. In the zebrafish Danio rerio, as well as in many other animals, several covariations have been established among behavioural, physiological and molecular responses. Nonetheless, not many studies have addressed the consistency in behavioural responses over time starting at the larval stage. Therefore, this study aimed to improve the understanding of behavioural consistency ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
(114 reference statements)
1
10
0
Order By: Relevance
“…We tested 60 groups (10 from each replicate line, 20 per treatment) or 480 fish in total. We conducted the assay every week from 8 to 22 days post fertilization or dpf (larval stages), at 45 dpf (juvenile), 61 and 85 dpf (subadult stages), and then every three weeks till 148 dpf and after six weeks at 190 dpf (adult stages) (Alfonso et al 2020 ). Behavioural changes in laboratory reared zebrafish is associated with morphological and physiological changes during larval (8–21 dpf), juvenile (21–60 dpf including metamorphosis around 45 dpf), subadult (60–90 dpf) and adult (90–190 dpf) stages (Alfonso et al 2020 ; Stednitz and Washbourne 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested 60 groups (10 from each replicate line, 20 per treatment) or 480 fish in total. We conducted the assay every week from 8 to 22 days post fertilization or dpf (larval stages), at 45 dpf (juvenile), 61 and 85 dpf (subadult stages), and then every three weeks till 148 dpf and after six weeks at 190 dpf (adult stages) (Alfonso et al 2020 ). Behavioural changes in laboratory reared zebrafish is associated with morphological and physiological changes during larval (8–21 dpf), juvenile (21–60 dpf including metamorphosis around 45 dpf), subadult (60–90 dpf) and adult (90–190 dpf) stages (Alfonso et al 2020 ; Stednitz and Washbourne 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted the assay every week from 8 to 22 days post fertilization or dpf (larval stages), at 45 dpf (juvenile), 61 and 85 dpf (subadult stages), and then every three weeks till 148 dpf and after six weeks at 190 dpf (adult stages) (Alfonso et al 2020 ). Behavioural changes in laboratory reared zebrafish is associated with morphological and physiological changes during larval (8–21 dpf), juvenile (21–60 dpf including metamorphosis around 45 dpf), subadult (60–90 dpf) and adult (90–190 dpf) stages (Alfonso et al 2020 ; Stednitz and Washbourne 2020 ). Though the maturation schedules of our size-selected lines are different with both the large-harvested and small-harvested line maturing earlier at smaller sizes than the controls (Uusi‐Heikkilä et al 2015 ), we tested them at the abovementioned stages to have an uniform experimental timeline (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Mean latency to exit the covered side of the GRT tank greatly varied over time, indicating that environment and/or age impact risk-taking behaviour. Although we are unable to identify causes of this variation, it supports that risk-taking behaviour is relatively plastic and can be affected by biotic or abiotic changes [25,40]. Nevertheless, within our studied population, individuals showed heterogeneous risk-taking behaviour which was moderately consistent over time and environmental conditions.…”
Section: Discussionmentioning
confidence: 61%
“…We observed moderate consistency in the latency to leave the initial area over a relatively long period of time (ICC = 0.38), and for whether fish left the initial area at all (ICC = 0.35). Previous studies have also demonstrated consistency in fish behaviour overtime within a population [15,40,47,48], but only few exceeded 45 days [26,47,49]. Long-term consistency in personality traits have, nevertheless, been studied in multiple mammal species.…”
Section: Discussionmentioning
confidence: 99%
“…The ontogenesis of the exploration-avoidance dimension has been more thoroughly investigated than boldness. Using emergence tests, some authors observed within-population differences in exploration-avoidance at very early stages of development (Alfonso et al, 2020;Edenbrow & Croft, 2011;Ibarra-Zatarain et al, 2020;Polverino et al, 2016), while other investigated its consistency along ontogeny (Alfonso et al, 2020;Castanheira et al, 2013;Edenbrow & Croft, 2011;Polverino et al, 2016). Fernandes-Silva et al (2022) observed that zebrafish separated by the time of egg hatching ("early hatchers" vs.…”
Section: Exploration-avoidancementioning
confidence: 99%